Family Disaster: The Origins of Gender Violence Legislation in Turkey - Alnıaçık, Ayşe (Violence against women, 2025)
This article provides a case study regarding struggles over framing gender violence as a political issue. It looks at how gender violence initially entered political discourse and state legislation in Turkey. It identifies the main political actors as feminists, Islamists, and Kemalists, and examines their impacts on state policy-making processes and outcomes. It argues that, in the Turkish context, the Islamism–Kemalism divide contoured the limits and possibilities of frame institutionalization in legislation and characterized state responses to gender violence through familial ideology, which prioritized family privacy and unity over women's right to live free from violence.